Chronicle of a Little Stage: a History of Café-Teatro Lima (1975-1989) in Gente Magazine (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This study focuses on the practice and trajectory of Café-Teatro, a form of stage production that was performed in Lima, Peru, during the 1970s and 1980s, told by the Peruvian Gente Magazine. Firstly, the article discusses its emergence in Lima's artistic milieu in the early 1970s, and the role that this magazine played in the dissemination and legitimization of this theatrical form. Secondly, it discusses the theatrical and thematic transformations that this scene underwent. It also discusses the participation of Gente Magazine in the recognition of the Argentine artist Vinko, whom the magazine named the King of Café-Teatro. This study shows how Gente Magazine addressed the decline of Lima's Café-Teatro and conveys how this variety of theatrical offerings gradually disappeared in the Peruvian capital.
Keywords: café-teatro; Gente Magazine; Vinko; Peru